Carpolobia lutea G. Don (Polygalaceae) Inhibits Inflammation and Oxidative Stress in an Acetic Acid Induced Model of Rat Colitis - Abiodun, O. O.; Oshinloye, A. O. (Drug Research, 2017)
Carpolobia lutea G. Don (CL) is used in folk medicine for the treatment of inflammatory disorders. Effort in this study is to evaluate the beneficial effect of the aqueous-methanol extract of leaf of CL in a rat model of acetic acid induced colitis. Male Wistar rats were distributed into 6 groups of 7 rats each; non colitic, untreated colitic and colitic rats treated with graded doses of CL (100–800 mg/kg). Rats were pre-treated for 2 days before colitis induction and thereafter for 7 days post colitic induction. 24 h after the last treatment, animals were sacrificed and colonic inflammation was evaluated both macroscopically and biochemically. Macroscopic damage score, weight/length ratio, myeloperoxidase (MPO) activity and tumor necrotic factor alpha (TNF-α) levels, were significantly higher in untreated colitic rats in comparison with non colitic rats (P<0.05). Treatment with CL significantly reduced the macroscopic damage scores, neutrophil infiltration (MPO activity) and TNF-α level (P<0.05). In addition, C. lutea significantly prevented depletion of colonic GSH and (SOD) levels (P<0.05). It appears that the beneficial effect of methanol extract of C. lutea leaf observed in this study is dose dependent and is related to its antioxidant and anti-inflammatory activity.
Keywords: Carpolobia lutea; colitis; rats; glutathione; superoxide dismutase; myeloperoxidase; tumour necrotic factor alpha (TNF-α)